Rapid thyroid nodule growth is not a marker for well-differentiated thyroid cancer. Issue 1 (December 2015) - Falch, Claudius; Axt, Steffen; Scuffi, Bettina; Koenigsrainer, Alfred; Kirschniak, Andreas; Muller, Sven
Abstract Background Rapid growth of thyroid nodules is described as being associated with thyroid cancer. The objective of the study was to determine how the growth rate of thyroid nodules during follow-up is associated with the risk of thyroid cancer. Methods Retrospective analysis of patients undergoing thyroid surgery for nodular disease and a repetitive preoperative ultrasound work-up of at least 6 months was done. Nodule growth was considered relevant when a volume increase >49 % was detected. Growth patterns were described as rapid for a volume increase present over 6 to 24 months. Results Of the 297 analysed patients, 226 (76 %) displayed relevant nodule growth and 71 (24 %) no relevant growth. A rapid growth pattern was seen in 73 patients (32 %). Well-differentiated thyroid cancer was diagnosed in 33 patients (11 %; 27 papillary, 6 follicular) with a relevant nodule growth in 2 and no relevant growth in 31 patients. No rapid growth pattern was observed in any case of well-differentiated thyroid cancer. A rapid growth pattern occurred only in benign nodules (70 patients) and in 1 patient each with a lymphoma, a metastasis of a renal cell cancer and a metastasis of a gastric adenocarcinoma. Therapy with levothyroxine and/or iodine was administered to 129 patients (43 %) and was significantly inversely correlated with nodule growth (odds ratio 0.27; CI 95 % 0.14–0.53, p < 0.001). Conclusions Thyroid nodule growth alone and especially a rapid growth pattern during follow-up for thyroid nodular disease is not a marker for well-differentiated thyroid cancer and should not be used as a stand-alone argument for thyroid surgery.